Introduction to information systems success in the 21st century - Gupta, Uma G. (Prentice Hall, 2000)
This introductory information systems book helps readers overcome the challenges of sorting through IS issues, concepts, and terms to maintain a current and relevant knowledge base in the midst of an information revolution. Chapter topics include IS use in business, computer hardware and software, databases for business applications, telecommunications, the internet, electronic commerce, client/server computing, managerial decision making, designing and developing IS systems, and computer security. For individuals with varying degrees of technical experience, interested in exploring the changes in the field of IS that are transforming society, business, and our personal lives.